Menyoal Akuntabilitas Dalam Desentralisasi Pengelolaan Keuangan Desa - Bakroh, David Syam Budi (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2019)
This study aims to describe financial management for Cangkudu Village for Budget Year 2018 under the Minister of Home Affairs Regulation 114/ 2014 about village financial management. The methods are the interview, observation, and document screening. This study found that Cangkudu Village has implemented villages financial management orderly. Nevertheless, there is some village’s revenues and expenditures that not yet included in the Budget Document. Its Financial Statement not yet discloses the budget realization completely. This study recommends Cangkudu Village to records any transactions completely so that information within financial management could be reliable and accountable. There is an issue about asset report format. It requires full disclosure for all assets, depreciation, and record the incremental asset value according to its capital expenditure realization for the current year